Biodegradable and Antioxidant DNA Hydrogel as a Cytokine Delivery System for Diabetic Wound Healing. Issue 21 (27th September 2022) - Wang, Zhenghao; Li, Wei; Gou, Liping; Zhou, Ye; Peng, Ge; Zhang, Jiayi; Liu, Jiaye; Li, Ruoqing; Ni, Hengfan; Zhang, Wanli; Cao, Ting; Cao, Qi; et al.
Abstract: Impaired diabetic wound healing is associated with the persistence of chronic inflammation and excessive oxidative stress, which has become one of the most serious clinical challenges. Wound dressings with anti‐inflammatory and reactive oxygen species (ROS)‐scavenging properties are desirable for diabetic wound treatment. In this study, a shape‐adaptable, biodegradable, biocompatible, antioxidant, and immunomodulatory interleukin‐33 (IL‐33)‐cytogel is developed by encapsulating IL‐33 into physically cross‐linked DNA hydrogels and used as wound dressings to promote diabetic wound healing. The porous microstructures and biodegradable properties of the IL‐33‐cytogel ensure the local sustained‐release of IL‐33 in the wound area, where the sustained‐release of IL‐33 is maintained for at least 7 days. IL‐33‐cytogel can induce local accumulation of group 2 innate lymphoid cells (ILC2s) and regulatory T cells (Tregs), as well as M1‐to‐M2 transition at the wound sites. Additionally, the antioxidant and biocompatible characteristics of DNA hydrogels promote the scavenging of intracellular ROS without affecting cell viability. As a result, local inflammation in the diabetic wound area is resolved upon IL‐33‐cytogel treatment, which is accompanied by improved granulation tissue regeneration and accelerated wound closure. This study demonstrates a promising strategy in tissue engineering and regenerative medicine by incorporating DNA hydrogels and cytokine immunotherapy for promoting diabetic wound healing. Abstract : Interleukin‐33 (IL‐33)‐cytogel facilitates sustained release of IL‐33 at wound sites and relieves local inflammation. Additionally, the DNA hydrogel itself improves the oxidative diabetic wound microenvironment by scavenging excessive reactive oxygen species. As a result, IL‐33‐cytogel improves granulation tissue regeneration and accelerates diabetic wound closure.